Toward a Theology of Inclusion for Those with Disabilities A Christian Response - Bunch, Wilton H. (2001)
People with disabilities, the largest minority in the United States, are frequently separated and marginalized from society. The congregation of Christian churches on Sunday morning does not reflect the prevalence of people with disabilities. The church should realize that Jesus' healing mission not only relieved disease, it integrated the person back into full membership of the community. Theology, which instructs the church's understanding as a community of believers, will benefit from critical reflection about disability. Our theological understanding of church and faith must also address the place of disability as a human experience.
Keywords: Disability; Ethics; Personhood; Theology